Towards a film literacy canon: identification and multicultural analysis of the contents used in film education with pre-university students in Spain (Communication & Society, 2019)
In the absence of a state film education plan in Spain, there are numerous initiatives operating in the field of both formal and non-formal education, the aim of which is pedagogy through cinema and about cinema. The European Commission has established the identification of a pantheon of authors of which knowledge is compulsory (canonical competence) as one of the four necessary competencies of this film literacy. This article aims to identify this canon promoted by the entities operating outside the formal curriculum and within the different contexts of non-formal education with early, primary and secondary education students in Spain. For this purpose, 65 entities (N=65) –educational centers, regional programs, museums, film libraries, film clubs, festivals, associations and foundations– have been catalogued and consulted for the first time in the different provinces of Spain. Among the results, 194 film titles and 142 names of directors used by those entities involved in image pedagogy in Spain have been collected. From a multicultural point of view, the analysis of the results points to the promotion of a biological approach to the history of universal cinema, in which national cinematography does not find a place. The primacy of North American and French productions is observed, as well as the absence of images with which to work on historical memory in Spain.